Comparison of equations for the estimation of head loss in polyethylene tube - Coelho, Anderson Prates [UNESP]; Zanini, Jose Renato [UNESP]; Faria, Rogerio Teixeira de [UNESP]; Dalri, Alexandre Barcellos [UNESP]; Palaretti, Luiz Fabiano [UNESP] (Univ Estadual Centro-oeste, 2018)
The determination of the head loss in irrigation projects is not used because it is a low practical method. For this, there are equations that estimate this variable, based on characteristics of the pipes material, diameter and system flow. Thus, the objective of this study was to evaluate the best equation for estimating the head loss in polyethylene tubing with internal diameter of 25 mm, comparing the results to the head loss determined in a mercury manometer. The experiment was carried out in the irrigation laboratory of the FCAV/Unesp, Jaboticabal, in June 2017. The estimation of the head loss was performed by the Hazen-Williams and Darcy-Weisbach equation, with the friction factor (f) estimated by Swamee and Jain and Blasius models. The equations were compared with the data determined in column of mercury in five flows, with values ranging from 1.55 m(3) h(-1) a 5.15 m(3) h(-1). The estimation of the head loss by Swamee and Jain method overestimated the values determined in the mercury column. Up to the 5.15 m(3) h(-1) flow the Hazen- Williams method presented the lowest variation and, consequently, the higher efficiency of estimated of head loss in relation to the values determined for polyethylene tubing with a diameter of 25 mm.
Keywords: External friction; Blasius; Hazen-Williams; Swamee and Jain